The Role Of Synbiotic Supplementation In Improving Bowel Movement Frequency In A Burn Patient With 32% Total Body Surface Area And Constipation: A Case Report - Cindy Herno Chrysela; Wina Sinaga; Aditya Wardhana; Diyah Eka Andayani (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Background: Severe burns cause microbiota dysbiosis, impaired intestinal motility, and constipation, worsening patient conditions and prolonging hospitalization. Research Objective: To evaluate the effectiveness of synbiotic supplementation in improving bowel movement frequency in burn patients. Case Illustration: A study conducted in the Burn High Care Unit at RSUPN Cipto Mangunkusumo involved a 42-year-old male patient with 32% TBSA burns and a history of kidney transplantation. Treatments included debridement, skin grafts, electrolyte correction, and synbiotic supplementation starting on day 6. During 29 days, energy intake, fiber intake, bowel movement frequency, and clinical status were monitored, showing significant improvements until discharge. Discussion: The 42-year-old male patient with 32% TBSA burns experienced impaired intestinal motility and constipation consistent with microbiota dysbiosis and decreased SCFA due to severe burns. The patient received enteral nutrition and Rillus® synbiotic supplementation from day 6, theoretically enhancing beneficial bacterial colonization and intestinal motility. Bowel movement frequency improved from day 7, indicating synbiotic-related benefits. Micronutrient supplementation according to ESPEN supported wound healing and immunity. Clinical condition and nutritional status improved with significant wound healing until discharge on day 30. Conclusion: Synbiotic supplementation effectively increased bowel movement frequency and improved intestinal function in severe burn patients with constipation. Keywords: Severe burn, microbiota dysbiosis, synbiotic, constipation, intestinal motility, bowel movement frequency.